Penyelesaian Sengketa Jual Beli Tanah Yang Masih Menjadi Hak Milik Bersama Namun Dijadikan Jaminan Hutang Di Bank(Studi Kasus Di Pengadilan Negeri Klaten) - Priyani, Arum, Nuswardhani, S.H, S.U (2017)
This study aims to determine the process of buying and selling land authorized by legislation, consideration of the judge in giving the conclusion of evidence and consideration of the judge in giving judgment on the case of the sale and purchase of land where the soil is still a common property and used as security for loans in the bank. Process results are legitimate land purchase is an agreement between the seller and the buyer and make the Sale and Purchase Agreements before PPAT, if there is a dispute in the court settlement is done starting from the filing of the lawsuit, the case investigation, evidence, and the judge's decision. Conclusion of proof by the judge is the sale and purchase lawful plaintiff, the plaintiff is the legal owner of the disputed land. Judge consideration in the decision making is the process of buying and selling land rights have to be light because it is done before PPAT this case in accordance with the legal system of the National Land and acts the defendant is against the law.